Overcoming Misconceptions of Elementary School Students in Energy Materials and Their Changes Using the Colorado PhET Application - Widyalistyorini, Dian; Nur Siyam, Isnaini; Fida Yanti, Wiwin; Setiawati Tri Rezeki, Irma; Julianto, Julianto; Rahmawati, Endah (Teknodika, 2024)
Given the critical role of energy in our daily lives and the increasing complexity of energy systems, addressing misconceptions about energy among elementary students is imperative for fostering energy literacy and responsible citizenship. This research aims to overcome elementary school (SD) students' misconceptions in understanding the concept of energy and its changes by using the PhET Colorado simulation application. Misconceptions in science learning at the basic level can hinder students' understanding of more complex concepts at the next level of education. The PhET Colorado app provides interactive simulations that allow students to learn through virtual experiments, thereby helping clarify concepts that are difficult to understand. This research uses an experimental method with a pretest-posttest control group design. Students were divided into two groups: an experimental group that used PhET simulations and a control group that used conventional learning methods. Data was collected through written tests and observation of learning activities. Data analysis was carried out by comparing the pretest and posttest results of the two groups to measure the increase in understanding of the concept of energy and its changes. The results showed that the use of the PhET Colorado simulation significantly improved students' understanding of the concept of energy and its changes. Students who study with PhET experience a greater reduction in misconceptions compared to students who study through conventional methods. These findings indicate that interactive simulation-based learning can be an effective strategy in overcoming misconceptions in elementary school students, as well as increasing their interest and motivation in learning science.